Financial Sector Assessment : Barbados - World Bank; International Monetary Fund (World Bank, Washington, DC, 2014)
The financial system faces a weak economic outlook and a deteriorating fiscal position posing substantial macroeconomic risks. As a result, sovereign risk has increased while the fixed exchange rate further limits policy options. The financial system has sizeable sovereign risk exposures and non-performing loans are rising although high capital and liquidity buffers in combination with strong parent entities mitigate risks. Credit unions appear more vulnerable. Since the 2008 financial sector assessment program (FSAP), the regulatory and supervisory framework has improved across all sectors. Consolidated risk-based supervision was introduced in the banking sector along with a formalization of supervisory methodologies. The government has committed a major adjustment package aimed at stabilizing international reserves and consolidating the fiscal position. Even if planned policies are successful, Barbados will continue to face challenging growth prospects, driven by weakened tourism markets, including Canada, the United Kingdom, and the United States; increased competition from other offshore jurisdictions; and appreciation of the real effective exchange rate.